ผลของการจัดหลักสูตรท้องถิ่นเพื่ออนุรักษ์เพลงพื้นบ้านสำหรับนักศึกษานอกระบบ สำนักงานส่งเสริมการศึกษานอกระบบและการศึกษาตามอัธยาศัย จังหวัดนนทบุรี - อัมพิกา แสงปิ่น (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research were (1) to develop local curriculum to conserve central Thai folk song for non – formal students in Nonthaburi provincial office of the non – formal and informal education. (2) to experiment the local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education. (3) to study participants’ satisfaction toward the organizing local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education. Populations of this research were local curriculum experts. The research was divided into 3 steps : 1. Development of local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education. 2. Experiment local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education. 3. Studying participants’ satisfaction toward the organizing local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education. The research findings were as follows : 1) The processes of developing local curriculum to enhance central Thai folk song conservation for non – formal education students in Nonthaburi provincial office of the non – formal and informal education based on Taba (1962) grass – root curriculum 7 procedures consists of object content organization of learning experiences and evaluation.2) The Score of knowledge skill and attitude increased higher than the prior experimental with statistic significant at level of .05 3) The experimental group was satisfied with the activities at high level.